2022
DOI: 10.1093/jrs/feac026
|View full text |Cite
|
Sign up to set email alerts
|

The Secret Life of Energy in Refugee Camps: Invisible Objects, Technologies, and Energy Systems in Humanitarianism

Abstract: Within humanitarian systems and refugee spaces, energy technologies are often invisible and unrecognized. Beyond basic UN and emergency interventions to supply solar lanterns, lie vibrant systems of connection underpinning refugee electricity and cooking access: a world of energy needs and provision exist within refugee camps in East Africa. The article frames energy within forced migration debates on technology: contributing to the social anthropology and migration studies literature by exploring the material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
3
3
0
Order By: Relevance
“…Further, a DQA was tailored and applied to assess the quality of the information achieved. The DQA revealed significant shortcomings on energy access in displacement contexts, a finding that coincides with statements from multiple publications from recent years [13,16,24]. The overall low-quality scores in the DQA are related to several reasons.…”
Section: Available Data On Energy Access In Displacement Contextssupporting
confidence: 76%
See 1 more Smart Citation
“…Further, a DQA was tailored and applied to assess the quality of the information achieved. The DQA revealed significant shortcomings on energy access in displacement contexts, a finding that coincides with statements from multiple publications from recent years [13,16,24]. The overall low-quality scores in the DQA are related to several reasons.…”
Section: Available Data On Energy Access In Displacement Contextssupporting
confidence: 76%
“…First, energy is needed to enable the operation of humanitarian actors, such as electricity in the offices of humanitarian organization and fuel for transportation [6,12]. Second, displaced persons have a wide range of energy needs that are embedded in basic areas of life [13], characterized by energy needs on a household level, such as for electricity and cooking, energy needs for income generating activities or businesses and energy needs on the community level, such as streetlights and the operation of public facilities such as schools and hospitals [13]. In this article, we focus on energy needs of displaced persons on an individual, household and community level as opposed to generalized energy needs that are associated with humanitarian operations.…”
Section: The Context Of Displacement and Access To Energymentioning
confidence: 99%
“…Further, a DQA was tailored to the specific needs of this study and utilized to assess the quality of the identified data sets.. The DQA revealed significant shortcomings in the quality of the data, which is in line with previous assessment (e.g., [13,16,24]). The overall poor results of the DQA can be attributed to several factors.…”
Section: Available Data On Energy Access In Displacement Contextssupporting
confidence: 65%
“…First, energy is needed to enable the operation of humanitarian actors, such as electricity in the offices of humanitarian organization and fuel for transportation [6,12]. Second, displaced persons have a wide range of energy needs that are embedded in basic areas of life [13], characterized by energy needs on a household level, such as for electricity and cooking, energy needs for income generating activities or for businesses and energy needs on the community level, such as streetlights and the operation of public facilities such as schools and hospitals [13]. In this article, we focus on energy needs of displaced persons on an individual, household and community level as opposed to generalized energy needs that are associated with humanitarian operations.…”
Section: The Context Of Displacement and Access To Energymentioning
confidence: 99%
“…First, energy is needed to enable the operation of humanitarian actors, such as electricity in the offices of humanitarian organizations and fuel for transportation [6,12]. Second, displaced persons have a wide range of energy needs that are embedded in basic areas of life [13], characterized by energy needs on a household level, such as electricity and cooking, energy needs for income-generating activities or for businesses and energy needs at the community level, such as streetlights and the operation of public facilities such as schools and hospitals [13]. In this While cumulative global statistics are relevant to highlight the increasing relevance of the subject matter, it is essential to acknowledge that the lived experiences of displaced persons vary greatly between different host countries and contexts.…”
Section: Introduction 1the Context Of Displacement and Access To Energymentioning
confidence: 99%